ASPECTS OF FINANCIAL AND ECONOMIC ACTIVITY AT EUROFIORE LLC, CELARU, DOLJ COUNTY (2011-2013) - Radu Lucian PÂNZARU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Celaru locality is located in Dolj County, located along the road that goes from Dăbuleni to Craiova, on the edge of the sand dunes that reach up here, extending from Jiu. The unit was established in 2010, having as main object of activity "growing cereals (except rice), legumes and oilseeds producing plant" - CAEN code 0111 from 12.07.2010. The study goal was to follow the constitution of the financial indicators (indicators of income, expenditure indicators, profitability indicators) the company analyzed their values and financial results. The working method is based on comparison in time of indicators so that the analysis was carried out based on a dynamic consists of three years, subjected to analysis, and the average of the period. The results show maximum for year 2013 - synthetic for the indicator and minimum one year 2012.